Telepharmacy service experience during the COVID-19 pandemic in the Republic of Srpska, Bosnia and Herzegovina - Amidžić, Rada (Archives of Pharmacy, 2022)
The COVID-19 pandemic has significantly affected health systems around the world. In addition, many health care services became unavailable to non-COVID patients. The study aimed to describe the remote pharmaceutical care service (telepharmacy) during the COVID-19 pandemic in the Republic of Srpska (RS), BiH. The RS Pharmaceutical Society appointed ten community pharmacists to provide telepharmacy services via telephone. After receiving the verbal permission, the pharmacists documented the topics discussed with the patients/users and pharmacist’s interventions, respectively. Prospective data collection was conducted from April 13 to May 21 2020. Descriptive and statistical analysis was performed using SPSS software (ver. 22). Data were collected for 71 patients/users, aged 25-85, while 50.7% were elderly (≥65 years). The prevalence of patients with chronic or acute/subacute conditions was 84.5%, and the proportion of users seeking health information about coronavirus or COVID-19 was 15.5%. Chronic diseases were the main reason for seeking consultations with pharmacists (74.6%), most often diseases of the cardiovascular (16.9%) and musculoskeletal system (15.5%). About 7% of chronic patients reported worsening of the chronic condition, and 9.9% reported only acute/subacute conditions. Most of the needs of patients/users were addressed by the pharmacist during the counseling, and only 15.5% of patients required referral to a doctor. The telepharmacy service proved to be a suitable model in the RS during the COVID-19 pandemic. Patients/users have expressed specific demands for community pharmacy services. Pharmacists have shown a high level of flexibility and ability to address the needs of patients in the emerging pandemic situation.